Blue or red? The effects of colour on the emotions of Chinese people. Issue 2 (June 2014) - Wang, Tingting; Shu, Siyun; Mo, Lei
<x xml:space="preserve">Abstract</x> Two experiments were performed to examine the effects of red and blue on the emotional pleasure of Chinese people. Experiment 1 explored the effects of the 'physical' colours red and blue on emotion, and the results showed that red induced positive and negative emotion, while blue only induced positive emotion. Experiment 2 further explored the effects of the 'verbal' colours red and blue on emotion, and the results showed that red induced only positive emotion, while blue induced neither positive nor negative emotion. The findings indicate that the influence of colour on emotion is rooted in both natural and social associations. For Chinese, the associations between blue and positive emotion, and red and negative emotion, were natural associations; however, the associations between red and positive emotion were social associations. Moreover, physical colour and verbal colour stimuli induced emotions by activating different mechanisms: physical colour induced emotions via both natural and social associations, whereas verbal colour induced emotions via social associations.